1996
DOI: 10.1093/oxfordjournals.humrep.a019372
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-binding proteins produced by Vero cells, human oviductal cells and human endometrial cells, and the role of insulin-like growth factor-binding protein-3 in mouse embryo co-culture systems

Abstract: Co-culturing embryos on helper cells can mimic the in-vivo environment, thereby enhancing embryo development in vitro. Insulin-like growth factors (IGF) and their binding proteins (IGFBP) also enhance embryo development. To investigate the kinds of IGFBP produced by various cell monolayers and the effects of IGFBP-3 on mouse embryo co-culture systems, 2-cell ICR mouse embryos were cultured in either human tubal fluid medium alone or in the presence of Vero cells, human oviductal cells or endometrial cells. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 48 publications
1
41
0
1
Order By: Relevance
“…Follistatin treatment increases TE formation in bovine blastocysts, whereas follistatin knockdown or activin A treatment decreases TE formation (92,93). Inhibitors of activin/nodal signaling are expressed in human fallopian tubes (94) and rat oviductal fluid (95,96), and human oviductal cells cause blastocyst formation in mouse embryos (97)(98)(99)(100)(101). Therefore, it is likely that inhibition of activin/nodal signaling has a role in TE formation in embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Follistatin treatment increases TE formation in bovine blastocysts, whereas follistatin knockdown or activin A treatment decreases TE formation (92,93). Inhibitors of activin/nodal signaling are expressed in human fallopian tubes (94) and rat oviductal fluid (95,96), and human oviductal cells cause blastocyst formation in mouse embryos (97)(98)(99)(100)(101). Therefore, it is likely that inhibition of activin/nodal signaling has a role in TE formation in embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Embryos co-cultured with various epithelial monolayers show improved development (Lai et al 1996). In such systems, IGFBP-1, -2, -3, -4 and -5 are produced by the monolayer helper cells (human endometrial and oviductal cells).…”
Section: Involvement Of Igfs/igfbps In Implantation -Interaction Betwmentioning
confidence: 99%
“…In such systems, IGFBP-1, -2, -3, -4 and -5 are produced by the monolayer helper cells (human endometrial and oviductal cells). Of these binding proteins, IGFBP-3 is the most prominent in co-cultured human endometrial monolayers and may play a role in embryo development either by regulating IGF actions or by directly enhancing embryo development (Lai et al 1996).…”
Section: Involvement Of Igfs/igfbps In Implantation -Interaction Betwmentioning
confidence: 99%
“…Dev. 54: [385][386][387][388][389][390] 2008) t has been suggested that the co-culture system exerts its beneficial effects by negative [1][2][3][4][5] or positive conditioning [4,[6][7][8][9][10][11] of the culture media, and by embryo-to-cell contact. Negative conditioning or detoxification is the ability of the feeder cells to remove deleterious components from the culture medium whereas positive conditioning is the ability of the feeder cells to modify it by releasing some components (embryotrophic factors) into the culture medium [12,13].…”
mentioning
confidence: 99%